Work issues on the job shortage and its impact - Pilar Isla Pera (Universidad de Alicante, 2012)
Sigerist stated, back in 1940, that disease is nothing but life under abnormal conditions. Nowadays millions of people suffer the drama of unemployment and job shortage and this compromises not only their ability to satisfy their primary needs, but also their personal dignity. Nevertheless, the concept of "work" is a profoundly historical category that has evolved to acquire different meanings, to the point of being considered an individual and social goal, the only means to promote oneself and relate to others, so that being "unemployed" is associated with personal and social degradation that can lead to the social discrimination of the unemployed and affect his or her physical, psychological and social health. This essay analyzes the current work crisis, its individual and social influence and its implications on human development and health. It discusses the main cultural perspectives on the notion of work and presents the hypothesis of a possible influence of the cultural meaning of the concept of "work" on diminishing self-esteem and mental health problems among unemployed people. The essay also highlights possible implications of the current situation in the future taking into consideration socioeconomic and political aspects as well as global demographic growth. Finally, the essay discusses the role that Public Health should have not only in the prevention and control of health problems among the unemployed, but also in the social, economic and cultural changes that are considered necessary to mitigate the serious social differences and to improve the current situation.